Interpreting Test Outcomes: A Comparative Study of Norm-Referenced and Criterion-Referenced Assessments - Herdah Herdah; Ainul Uyun; Raodhatul Jannah (Edumaspul: Jurnal Pendidikan, 2024)
Learning is a dynamic process involving interaction among students, educators, and learning resources within a structured environment aimed at enhancing understanding and competence. Beyond knowledge transfer, educators play a crucial role in preparing students for learning by assessing situational readiness and optimizing learning conditions. Post-learning, evaluations are imperative to gauge goal attainment and guide improvement strategies, employing measurement and assessment techniques. Student capabilities and teaching efficacy benefit from evaluation, with assessments extending to norm-referenced (PAN) and criterion-referenced (PAK) methodologies. PAN compares individual achievements against group norms, facilitating performance ranking within a cohort. Conversely, PAK utilizes predetermined benchmarks to determine academic success. This literature review synthesizes prior studies on PAN and PAK methodologies. Noteworthy studies include processing techniques discussed by Alfath and Raharjo (2019), implementation insights by Aliyam, Dayanti, and Mukaffa (2021), and completeness criteria exploration by Pangastuti and Munfa'ati (2018). The review employs a descriptive analysis approach, utilizing educational and curriculum literature to inform its findings. The study concludes that PAN offers comparative insights into student performance within a group context, while PAK sets clear benchmarks for academic achievement. This study underscores the significance of evaluation in educational settings, advocating for effective evaluation tools to optimize learning strategies and enhance student engagement.